1998
DOI: 10.1080/00288233.1998.9513335
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between body condition score and body composition in dairy cows

Abstract: The relationship between body condition score and physically dissected body composition was assessed in forty cull Friesian and Friesian-cross cows. Body condition score was assessed using the New Zealand condition scoring system which is based on the contours of the cow from its hooks to its hocks. Measurements following slaughter included the weights of the udder, kidney knob and channel fat, omental fat, and mesenteric fat, the post-mortem thickness of the dewlap, the dentition, and carcass length. The prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 14 publications
2
26
0
1
Order By: Relevance
“…The greater BW increase per unit of BCS increase during the DP (35 kg per BCS unit) is expected because a signifi cant part of BW change in this stage can be accounted for by conceptus growth (which can account for 0·15 of total BW), mammary gland tissue development, and increased blood volume (Agricultural and Food Research Council, 1998). Additionally, the typical intake reduction Garnsworthy and Topps, 1982;Wright and Russel, 1984a;Garnsworthy and Jones, 1987;Jones and Garnsworthy, 1987;Chilliard et al, 1991;Otto et al, 1991;Gregory et al, 1998). Among the highest estimates of BW per unit BCS available in the literature are the estimates of Otto et al (1991), later used to validate the current National Research Council model (Fox et al, 1999), and the estimate of Wright and Russel (1984a) based on non-lactating and non-pregnant dairy cows, which showed a large amount of data variation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The greater BW increase per unit of BCS increase during the DP (35 kg per BCS unit) is expected because a signifi cant part of BW change in this stage can be accounted for by conceptus growth (which can account for 0·15 of total BW), mammary gland tissue development, and increased blood volume (Agricultural and Food Research Council, 1998). Additionally, the typical intake reduction Garnsworthy and Topps, 1982;Wright and Russel, 1984a;Garnsworthy and Jones, 1987;Jones and Garnsworthy, 1987;Chilliard et al, 1991;Otto et al, 1991;Gregory et al, 1998). Among the highest estimates of BW per unit BCS available in the literature are the estimates of Otto et al (1991), later used to validate the current National Research Council model (Fox et al, 1999), and the estimate of Wright and Russel (1984a) based on non-lactating and non-pregnant dairy cows, which showed a large amount of data variation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is worth noting that at BCS of less than 1·5 it was extremely diffi cult to maintain a good contact between the ultrasound transducer and the hide of the animal, which together with the relatively thin layer of subcutaneous fat limited the measurement accuracy. It has been noted that when body fatness is low, the non-lipid components increase their contribution to adipose tissue weight (Gregory et al, 1998), and variations in tissue water are also higher (Otto et al, 1991). The thin BF layer of poorly conditioned cows could have contributed to the weaker association between BCS and BF in experiment 1 and the interactions with experiment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wright and Russel (1984) found that BCS is a poor predictor of inter-and intramuscular fat, which together account for 35 to 45% of body fat (Roche et al, 2009). However, the proportion of subcutaneous fat is highly correlated with total body fat (Butler-Hogg et al, 1985) such that BCS is more useful as an assessment of a relative, rather than absolute, change in body fat (Gregory et al, 1998). Body condition score may be less accurate in thin cows with little subcutaneous fat, and it may be more difficult to assess subcutaneous fat levels accurately in obese cows (Roche et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that, although it is a subjectively measured trait, BCS is accurate enough to explain a large part of the variation in body reserves between animals (Waltner et al, 1994;Enevoldsen and Kristensen, 1997;Gregory et al, 1998). Body condition score meets all the criteria to be considered a useful indicator trait for health and fertility status in dairy cattle.…”
Section: Introductionmentioning
confidence: 99%